2015
DOI: 10.5204/mcj.1024
|View full text |Cite
|
Sign up to set email alerts
|

Digitods: Toddlers, Touch Screens and Australian Family Life

Abstract: Introduction Children are beginning to use digital technologies at younger and younger ages. The emerging trend of very young children (babies, toddlers and pre-schoolers) using Internet connected devices, especially touch screen tablets and smartphones, has elicited polarising opinions from early childhood experts. At present there is little actual research about the risks or benefits of tablet and smartphone use by very young children. Current usage recommendations, based on research into passive television … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 1 publication
0
25
0
3
Order By: Relevance
“…We continue to witness the growing social phenomenon of the mediatization of childhood , wherein the media and the institutions behind them permeate all aspects and levels of children’s personal and social lives (Krotz, 2007). This phenomenon became even more prominent as mobile media turned interactive: the introduction of the iPhone in 2007 marked the birth of the digitods— a new generation of children born with ready access to a vast range of mobile touchscreen devices (Holloway, Green, & Stevenson, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We continue to witness the growing social phenomenon of the mediatization of childhood , wherein the media and the institutions behind them permeate all aspects and levels of children’s personal and social lives (Krotz, 2007). This phenomenon became even more prominent as mobile media turned interactive: the introduction of the iPhone in 2007 marked the birth of the digitods— a new generation of children born with ready access to a vast range of mobile touchscreen devices (Holloway, Green, & Stevenson, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Young children are increasingly exposed to mobile media given the mediatization of childhood, wherein the media and the institutions behind them permeate all aspects and levels of children's personal and social lives (Krotz, 2007;Livingstone, 2014;Paus-Hasebrink, Kulterer, & Sinner, 2019). This phenomenon became even more prominent as mobile media turned interactive: The introduction of the iPhone in 2007 marked the birth of the Digitods -a new generation of children born with ready access to a vast range of mobile touchscreen media (Holloway, Green, & Stevenson, 2015). In the United States, for example, recent surveys reported that 97% of children aged 0-8 live in a home with some type of mobile device, while 48% of children have their own mobile device (Rideout & Robb, 2020).…”
Section: The Role Of Interactive Mobile Media In Children's Livesmentioning
confidence: 99%
“…The possibility of posting voice queries comes at a time when the age of first encounter with the Internet among children is becoming younger. Touchscreens enable toddlers and young children to operate smartphones and tablets independently, bypassing the need for a computer mouse that is often challenging for them (Holloway et al, 2015). The integration of voice queries overcomes another major barrier: that of writing in general and operating of keyboards in particular.…”
Section: From Passive To Active Exposure To Knowledgementioning
confidence: 99%